Pseudomonas fluorescens as a Biocontrol Agent for Controlling Various Plant Diseases - Beni Gusnadi; Linda Advinda; Azwir Anhar; Irma Leilani Eka Putri; Moralita Chatri (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Biological control or biocontrol is a way that involves organisms to reduce the growth of pathogens and reduce the impact of disease. The use of biocontrol agents is an alternative to control plant disease-causing pathogens. One of the biocontrol agents that can be used is Pseudomonas fluorescens. Basically P. fluorescens is the largest group producing antibiotics and antimicrobial compounds of cyanide acid (HCN) and siderophores. The compounds it produces can inhibit activity and control pathogens. Therefore, P. fluorescens has great potential as a biocontrol agent for controlling plant diseases. This study aims to collect and analyze articles related to P. fluorescens as a biocontrol agent for controlling various plant diseases. This type of research is research that uses internet sources from the Google Scholar database. The stages consist of identification, screening, eligibility and acceptance. Based on the articles collected, it was found that P. fluorescens is a biocontrol agent that can control various plant diseases. Biocontrol agents influence the activity and growth of pathogens thanks to the compounds they produce